Development of Moldova psychological services market: the need to use regulatory mechanisms and foreign European partnership - Elena RAILEAN; Irina VARBAN (Eastern European Journal of Regional Studies, 2020)
The article reflects the features of the formation and development of the market of psychological services in Moldova, which were identified as a result of a survey of psychologists in the country. The reasons for increasing demand and expanding supply in the market are explained. Problems and difficulties in the functioning of the market of psychological services were revealed, such as the lack of a legislative framework, price regulation, state support, and the quality of psychological services. The article highlights the ways and mechanisms for the effective development of Moldova psychological services market, the need to use regulatory mechanisms and foreign European partnership.